EDUREADER: INOVASI DIGITAL READING UNTUK PEMBELAJARAN ORANG DEWASA DENGAN LOW VISION DI PERGURUAN TINGGI MENGGUNAKAN PENDEKATAN ANDRAGOGIS MENUJU PEMBELAJARAN AKSESIBEL - Putra, Ari; Ulfasari, Nia; Ramadhani Dewi, Putri; Velisa, Mutiara (IKIP Siliwangi, 2026)
An andragogical approach is essential to address the unique characteristics of pembelajar dewasa with visual impairments. This study aimed to develop and evaluate of the EduReader application as a digital reading innovation incorporating andragogical principles for students with low vision in the higher education Universitas Bengkulu. The research employed a single case study design with a qualitative approach enriched by quantitative data. Research participants included one low vision student in the fifth semester and two course instructors. Data were collected through intensive observation, in-depth interviews, comprehension assessments, self-assessment instruments, and usage log analytics over a 16-week implementation period. The andragogical approach was operationalized through self-directed learning principles, experiential learning, and problem-centered approaches integrated within the application features. Results demonstrated significant transformation in the subject's learning autonomy. Self-directed learning readiness scores increased from 67 to 89 (scale 100), with the highest gains in self-management (46.6%) and self-control (48.4%) dimensions. Learning autonomy improved from 52 to 94/100, while comprehension of leadership materials increased by 45% based on portfolio assessment. Usage analytics revealed high consistency with an average daily usage of 2.3 hours and a 94% completion rate. Personalization features including adaptive reading speed, customizable interface, and voice preferences effectively supported andragogical principles by providing pembelajar with complete control. The study concludes that EduReader is effective as a digital reading innovation supporting andragogical learning for pembelajar dewasa with low vision. The technology-facilitated self-directed learning approach successfully generated fundamental transformation from external dependency toward authentic learning autonomy